Slave-women, according to Altanokhy’s book" Relief after Severity - Hindawi, Hanadi Za'al (Journal of Humanities & Social Sciences, 2021)
This research paper aimed at presenting the traces of Altanokhy’s book (Relief after severity) from a historic, political, social and economic perspectives and methodology. upon which the author relied on texts, also, based on artistic and literary elements which reflect the political era and the characteristics of AlTanokhy’s personality. The research paper deals elaborately and redundantly with the topic of slave-women. from the perspective of Altanokhy in his book "Relief after Severity". Almost all nations had the knowledge of possessing women as slaves, and this wasn’t restricted only to caliphs but also by their followers, the luxurious, high -class princes and their people. Hence palaces were full of slave-women. Altanokhy,in his book, had mentioned the prices of these women and the trade of them by the merchants of slaves ,also he mentioned the places of them, which were called (homes of slaves and maids. ) The role of slave-women. was not only restricted to singing, but it exceeded to excelling in different branches of science, The Holy Qura’an , literature and poetry ,besides other household chores and serving palaces or houses including cutting wood and carrying water. Furthermore, these women had a great influence on caliphs, ministers and the public.